Khusyu' in the Perspective of Quraish Shihab: A Study of Tafsir al-Misbah - Ridwan, Rahmad (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to understand the meaning of khusyu’ in the Qur'an and examine Quraish Shihab's perspective on this concept. Using a library research method, the study analyzes verses related to khusyu’ alongside relevant literature. The research data consists of primary sources, such as Tafsir al-Mishbah and Pesan, Kesan, dan Keserasian Al-Qur’an by M. Quraish Shihab, as well as secondary sources, including books and writings that discuss similar topics. In the Qur'an, the term khusyu’ appears in various forms, such as khasya’at, khusyū’an, khāsyi’ūna, and others, which can be categorized into seven aspects: khusyu’ in prayer, in all conditions, in accepting God's truth, concerning the Day of Judgment and the Hereafter, as the submission of the universe, as a state inherent in both men and women, and in worship and supplication. This analysis provides a comprehensive understanding of khusyu’ as described in the Qur'an and interpreted by Quraish Shihab.